2011
DOI: 10.1097/jgp.0b013e3181faec23
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Cognitive, Functional, and Neuropsychiatric Symptom Domains in a Population Cohort With Alzheimer Dementia: The Cache County Dementia Progression Study

Abstract: Objectives-Progression of Alzheimer's dementia (AD) is highly variable. Most estimates derive from convenience samples from dementia clinics or research centers where there is substantial potential for survival bias and other distortions. In a population-based sample of incident AD cases, we examined progression of impairment in cognition, function, and neuropsychiatric symptoms, and the influence of selected variables on these domains. Design-Longitudinal, prospective cohort study Setting-Cache County (Utah)P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
209
5
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(246 citation statements)
references
References 45 publications
29
209
5
3
Order By: Relevance
“…All study researchers underwent online training and were certified as "CDR raters" [20] before scoring the CDR based on all information available from the baseline assessments. In accordance with other studies assessing progression in dementia with CDR-SB [6,8], patients who had an increase of less than 1 point in the CDR-SB score per year of follow-up were regarded as slow progressors.…”
Section: Outcome Measuresmentioning
confidence: 77%
See 3 more Smart Citations
“…All study researchers underwent online training and were certified as "CDR raters" [20] before scoring the CDR based on all information available from the baseline assessments. In accordance with other studies assessing progression in dementia with CDR-SB [6,8], patients who had an increase of less than 1 point in the CDR-SB score per year of follow-up were regarded as slow progressors.…”
Section: Outcome Measuresmentioning
confidence: 77%
“…A population-based study found that 30-58% of the participants with AD declined slowly, with a yearly change of less than one point on the CDR-SB and the MMSE [6]. Consistent with this finding, two memory clinic studies found that 25-30% of the patients were stable over a period of two to three years [5,8].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Tschanz et al 8 found that a significant proportion of persons with AD progresses slowly and suggest ongoing need to identify factors that may slow the progression of AD. Other studies have noted faster rates of progression in high CR patients after the diagnosis of AD 3,9,10 .…”
Section: Introductionmentioning
confidence: 99%